1957
DOI: 10.1139/f57-003
|View full text |Cite
|
Sign up to set email alerts
|

The Smaller Cetacea of Eastern Canadian Waters

Abstract: An account is given of the known records, distribution and migrations of the smaller Odontocete whales occurring in eastern Canadian waters, with measurements of specimens obtained of the rarer species. The distribution of the abundant pilot whale Globicephala melaena (Traill) has been studied in most detail. The species' summer range includes both the offshore waters of the Labrador Sea and the coastal waters around Newfoundland. The coastal population feeds only on the squid Illex illecebrosus (LeSueur) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 4 publications
3
80
0
1
Order By: Relevance
“…Comparable data for porpoise from Newfoundland are limited; Sergeant and Fisher (1957) reported a 127 cm male while Sergeant et al (1970) examined two porpoises, a female weighing 50 kg and a juvenile of unidentified gender at 18 kg. A porpoise, 79 cm long and 7.7 kg was found in the stomach of a Greenland shark, Somniosus microcephalus, caught on the Grand Banks of Newfoundland (Williamson 1963).…”
Section: Nammco Scientific Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable data for porpoise from Newfoundland are limited; Sergeant and Fisher (1957) reported a 127 cm male while Sergeant et al (1970) examined two porpoises, a female weighing 50 kg and a juvenile of unidentified gender at 18 kg. A porpoise, 79 cm long and 7.7 kg was found in the stomach of a Greenland shark, Somniosus microcephalus, caught on the Grand Banks of Newfoundland (Williamson 1963).…”
Section: Nammco Scientific Publicationsmentioning
confidence: 99%
“…Fontaine et al 1994, Kingsley andReeves 1998), information on the Newfoundland population is extremely limited. Sergeant and Fisher (1957) describe harbour porpoise distribution around Newfoundland and Labrador, while morphological data are limited to lengths and weights of a small number of samples (Sergeant and Fisher 1957, Williamson 1963, Sergeant et al 1970. To date, no harbour porpoise abundance surveys have been conducted in Newfoundland waters.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a Popelogan River in Restigouche County, northern New Brunswick he was referring to the Pocologan River in southern New Brunswick. The white whale occurs in eastern arctic waters from Ellsmere Island through Davis Strait to James Bay, along the (Fisher and Sergeant, 1954), probably an offshoot of the St. Lawrence River population (Sergeant and Fisher, 1957 Dawson, p. 268. 1905 Delphinapterus leucas Pallas; Lambe, p. 39.…”
Section: Review Of Previous Records From New Brunswickmentioning
confidence: 99%
“…Sergeant and Fisher (1957) suggested that belugas may stray from the St. Lawrence River population. Although harp seals are not known to breed in the Bay of Fundy, rare occurrences are known (McAlpine and Walker, in press).…”
Section: Paleoclimatic Significancementioning
confidence: 99%
“…THE ommastrephid squid Illex illecebros~~s, a summer migrant to inshore Newfoundland waters, is an important prey item for many species of whales (Sergeant 1962;Sergeant and Fisher 1957;Squires 1957), seabirds (Ennis and Collins 1978). and for many species of fish (Vinogradov 1 972;Butler 197 1 ;Squires 1957;Templeman 1944).…”
mentioning
confidence: 99%